A composite scale inhibitor for chemical wastewater treatment and its preparation method and application
By mixing polyethylene glycol modified chitosan with EDTA-chitosan with polyacrylic acid and citric acid, a composite scale inhibitor suitable for chemical wastewater treatment was prepared, and the existing scale inhibitor was solved at high temperature and The problem of decreasing scale resistance effect in a multi-metal ion environment has achieved the effect of effectively preventing scale formation and accumulation in chemical wastewater.
Patent Information
- Application Number
- CN202411013322.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing scale inhibitors are difficult to adapt to complex water quality conditions in chemical wastewater treatment, especially in the presence of high temperatures and a variety of metal ions. The scale inhibition effect is significantly reduced and cannot effectively prevent the formation and accumulation of scale.
Compound scale inhibitors are prepared by mixing polyethylene glycol-modified chitosan and EDTA-chitosan with polyacrylic acid and citric acid. Polyethylene glycol-modified chitosan is prepared by etherification graft modification method, and the Maintain good scale resistance under different water quality conditions.
This composite scale inhibitor maintains excellent scale inhibition effect in high temperature and the presence of various metal ions. It is suitable for a variety of water treatment systems, and is environmentally friendly and pollution-free. The preparation method is simple and easy to industrially produce.
Smart Images

Figure CN118684359B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a composite scale inhibitor for chemical wastewater treatment and a use method thereof. Background Art
[0002] Scale inhibitors are a type of chemical agent that is mainly used to prevent or reduce the formation of scale. They disperse insoluble inorganic salts in water, prevent or interfere with the precipitation and scaling of these salts on the metal surface, thereby maintaining good heat transfer effects of metal equipment.
[0003] The mechanism of action of scale inhibitors mainly includes chelation, dispersion, lattice distortion, etc. Scale inhibitors can be divided into many types, including organic phosphate scale inhibitors, polycarboxylic acid scale inhibitors and dispersants, etc. These scale inhibitors are widely used in water treatment, cooling water systems, boiler water treatment and other fields.
[0004] However, most of the existing scale inhibitors are difficult to adapt to the needs of chemical wastewater treatment. The main reason is that the composition of chemical wastewater is complex and changeable, and scale inhibitors lack wide adaptability and cannot maintain a stable scale inhibition effect under different water quality conditions. Generally, chemical wastewater contains a large amount of metal ions, and high-temperature operation may be involved in the chemical wastewater treatment process. Metal ions and high temperature are one of the important factors affecting the effect of scale inhibitors. The scale inhibition performance of most existing scale inhibitors will drop significantly with the increase of metal ion content and the increase of temperature. Therefore, the development of a scale inhibitor that can simultaneously overcome the adverse effects of temperature increase and metal ions has an important impact on chemical wastewater treatment. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a composite scale inhibitor for chemical wastewater treatment and its preparation method and application. The present invention uses polyethylene glycol-modified chitosan and EDTA-chitosan mixed with polyacrylic acid and citric acid to prepare a composite scale inhibitor. The composite scale inhibitor of the present invention treats wastewater containing multiple metal ions and still has good scale inhibition performance under high temperature conditions.
[0006] The composite scale inhibitor of the present invention comprises the following raw materials in parts by weight:
[0007] 2-10 parts of polyethylene glycol-modified chitosan, 5-30 parts of EDTA-chitosan, 10-25 parts of polyacrylic acid, 2-8 parts of citric acid, and 80-100 parts of water.
[0008] Further, the weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:(3-5). Preferably, the weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:5.
[0009] Furthermore, the composite antiscalant comprises the following raw materials in parts by weight:
[0010] 5 parts of polyethylene glycol-modified chitosan, 25 parts of EDTA-chitosan, 15 parts of polyacrylic acid, 5 parts of citric acid, and 85 parts of water.
[0011] Furthermore, the polyethylene glycol-modified chitosan is prepared by using polyethylene glycol and chitosan as raw materials and undergoing etherification grafting modification.
[0012] Furthermore, the preparation method of the polyethylene glycol-modified chitosan comprises the following steps:
[0013] S1, adding chitosan to an alkaline solution, stirring for reaction, filtering, and freeze-drying;
[0014] S2, dissolving phthalic anhydride in DMF to obtain a phthalic anhydride solution, slowly adding the freeze-dried chitosan in S1 to the phthalic anhydride solution, stirring the reaction mixture, pouring it into an ice alcohol solution, filtering it after precipitation, washing the precipitate with an alcohol solution until no reactant remains, and vacuum drying it to obtain phthalated chitosan;
[0015] S3, adding thionyl chloride and phthalated chitosan to pyridine, stirring for reaction and then cooling, filtering the precipitate, and vacuum drying the precipitate to obtain chlorinated chitosan;
[0016] S4, adding sodium hydride to anhydrous tetrahydrofuran, adding methoxy polyethylene glycol, stirring once to deprotonate the methoxy polyethylene glycol, then slowly adding chlorinated chitosan, stirring twice, pouring into an ice alcohol solution after the reaction is completed, filtering after precipitation, and vacuum drying to obtain polyethylene glycol phthalyl chitosan;
[0017] S5. Add polyethylene glycol-modified phthalyl chitosan to a sodium hydroxide solution, stir for reaction, neutralize the reaction solution dropwise with dilute hydrochloric acid until it is neutral, then add the reaction mixture to an ice alcohol solution for precipitation, wash the precipitate with an alcohol solution to remove residual alkali and by-products, and vacuum dry to obtain polyethylene glycol-modified chitosan.
[0018] Furthermore, the alkaline solution in S1 is a sodium hydroxide solution or a potassium hydroxide solution.
[0019] Furthermore, the concentration of the alkaline solution is 40wt% to 50wt%.
[0020] Furthermore, the reaction temperature in S1 is 80° C. to 110° C., and the reaction time is 4 to 12 hours.
[0021] Furthermore, the weight-to-volume ratio of the chitosan to the alkaline solution is 1 g:(20-50) mL. Preferably, the weight-to-volume ratio of the chitosan to the alkaline solution is 1 g:25 mL.
[0022] Furthermore, the concentration of the phthalic anhydride solution in S2 is 1 mol / L.
[0023] Further, the reaction temperature in S2 is 110°C to 120°C, and the reaction time is 6 to 10 hours. Preferably, the reaction temperature in S2 is 120°C, and the reaction time is 6 hours.
[0024] Furthermore, the weight-to-volume ratio of the freeze-dried chitosan to the phthalic anhydride solution in S2 is 1 g:(10-30) mL. Preferably, the weight-to-volume ratio of the freeze-dried chitosan to the phthalic anhydride solution in S2 is 1 g:20 mL.
[0025] Furthermore, the mass ratio of thionyl chloride to phthalated chitosan in S3 is (5-10): 1. Preferably, the mass ratio of thionyl chloride to phthalated chitosan in S3 is 8:1.
[0026] Further, the weight volume ratio of thionyl chloride to pyridine in S3 is 1 g: (15-30) mL. Preferably, the weight volume ratio of thionyl chloride to pyridine is 1 g: 20 mL.
[0027] Further, the reaction temperature in S3 is 50°C to 100°C, and the reaction time is 30 to 60 minutes. Preferably, the reaction temperature in S3 is 80°C, and the reaction time is 45 minutes.
[0028] Further, the weight volume ratio of the sodium hydride to anhydrous tetrahydrofuran is (0.1-0.5) g / L. Preferably, the weight volume ratio of the sodium hydride to anhydrous tetrahydrofuran is 0.2 g / L.
[0029] Further, in said S4, the stirring temperature is 50°C to 70°C, and the stirring time is 0.5 to 3 hours. Preferably, in said S4, the stirring temperature is 50°C, and the stirring time is 2 hours.
[0030] Furthermore, the secondary stirring temperature in S4 is 50°C to 70°C, and the stirring time is 10 to 20 hours. Preferably, the primary stirring temperature in S4 is 50°C, and the stirring time is 12 hours.
[0031] Furthermore, the concentration of the sodium hydroxide solution in S4 is 4wt%.
[0032] Furthermore, the weight-to-volume ratio of the polyethylene glycolized phthalyl chitosan to the sodium hydroxide solution in S4 is (3-4) mg:1 mL. Preferably, the weight-to-volume ratio of the polyethylene glycolized phthalyl chitosan to the sodium hydroxide solution in S4 is 3 mg:1 mL.
[0033] Further, the reaction temperature in S4 is 80°C to 90°C, and the reaction time is 2 to 10 hours. Preferably, the reaction temperature in S4 is 85°C, and the reaction time is 8 hours.
[0034] Furthermore, the alcohol solution is anhydrous ethanol or anhydrous methanol.
[0035] Furthermore, the preparation process of the polyethylene glycol-modified chitosan is carried out in an inert gas environment.
[0036] Furthermore, the preparation method of the EDTA-chitosan is as follows:
[0037] Chitosan was dissolved in acetic acid solution, EDTA-2Na was added, the pH value was adjusted to 5.0 with 5 mol / L sodium hydroxide solution, carbodiimide (EDAC) was added, stirred for reaction, and then the reaction solution was dialyzed and freeze-dried to obtain EDTA-chitosan.
[0038] Furthermore, the concentration of the acetic acid solution is 0.1% to 3% (v / v).
[0039] Furthermore, the weight-to-volume ratio of the chitosan to the acetic acid solution is 0.1 g:1 mL.
[0040] Furthermore, the weight ratio of chitosan to EDTA-2Na is 1:2.
[0041] Furthermore, the reaction temperature is room temperature and the reaction time is 4 hours.
[0042] Furthermore, the concentration of the carbodiimide is 40 mmol / L.
[0043] The present invention also provides a method for preparing the composite antiscalant, which specifically comprises the following steps:
[0044] Weigh the raw materials according to the proportion, mix them evenly and stir them to obtain the composite scale inhibitor.
[0045] Furthermore, the stirring temperature is 20°C to 50°C, and the stirring time is 5 to 15 minutes.
[0046] The composite scale inhibitor of the present invention is used for treating chemical wastewater, and the usage amount is 20-100 mg / L.
[0047] Compared with the prior art, the beneficial technical effects of the present invention are:
[0048] A certain amount of polyethylene glycol-modified chitosan and EDTA-chitosan are added to the composite scale inhibitor of the present invention, so that the composite scale inhibitor can effectively prevent the formation and accumulation of scale and can show excellent scale inhibition effect under different water quality conditions.
[0049] The composite scale inhibitor of the present invention is less affected by metal ions and still has good scale inhibition performance in the presence of metal ions such as magnesium, aluminum, and iron.
[0050] The raw materials used in the present invention will not cause pollution to the environment and are green and environmentally friendly.
[0051] The composite scale inhibitor of the present invention is suitable for various water treatment systems, including industrial cooling water systems, boiler water systems, etc., and can maintain good scale inhibition performance under different temperature and pH conditions.
[0052] The preparation method of the composite antiscalant of the present invention is relatively simple and easy to industrialize and produce. Through reasonable process steps and condition control, high-quality antiscalant products can be stably obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] The present invention will be further described below in conjunction with the accompanying drawings.
[0054] Figure 1 is the scale inhibition rate of the composite scale inhibitor at different temperatures. DETAILED DESCRIPTION
[0055] The present invention provides a composite scale inhibitor, which specifically comprises the following raw materials in parts by weight:
[0056] 2-10 parts of polyethylene glycol-modified chitosan, 5-30 parts of EDTA-chitosan, 10-25 parts of polyacrylic acid, 2-8 parts of citric acid, and 80-100 parts of water.
[0057] In one embodiment, the weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:(3-5).
[0058] In one embodiment, the weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:5.
[0059] The present invention strictly limits the ratio of polyethylene glycol-modified chitosan and EDTA-chitosan, because under a specific ratio, the two can play a good synergistic role, maximize the scale inhibition effect, and ensure that the scale inhibitor will not be poisoned. In addition, the preparation method of polyethylene glycol-modified chitosan is more complicated than EDTA-chitosan, and the cost is relatively high. Strict ratio can optimize the use of raw materials, reduce production costs, and reduce the use of high-cost raw materials while ensuring the scale inhibition effect, thereby improving economic benefits. Studies have shown that a good scale inhibition effect can be achieved when the weight ratio of polyethylene glycol-modified chitosan to EDTA-chitosan is within the range of 1: (3 to 5). Within this range, as the content of polyethylene glycol-modified chitosan increases, the stability and service life of the scale inhibitor are slightly improved, but overall they are within a good acceptable range. Therefore, the present invention further limits the weight ratio of polyethylene glycol-modified chitosan to EDTA-chitosan to 1: 5, that is, within an acceptable range, the least polyethylene glycol-modified chitosan is used to prepare a composite scale inhibitor with better comprehensive performance and the lowest cost. It is also worth noting that studies have shown that when the content of polyethylene glycol-modified chitosan is increased beyond the range specified in the present invention, the scale inhibition performance of the composite scale inhibitor not only does not increase, but also tends to decrease further. Therefore, even if you want to increase the stability and service life of the composite scale inhibitor by increasing the content of polyethylene glycol-modified chitosan, you must strictly control it within the range specified in the present invention.
[0060] In one embodiment, the composite antiscalant comprises the following raw materials in parts by weight:
[0061] 5 parts of polyethylene glycol-modified chitosan, 25 parts of EDTA-chitosan, 15 parts of polyacrylic acid, 5 parts of citric acid, and 85 parts of water.
[0062] In one embodiment, the method for preparing polyethylene glycol-modified chitosan comprises the following steps:
[0063] S1. Add chitosan into alkaline solution, stir for reaction, filter and freeze-dry.
[0064] The present invention utilizes the effect of alkaline solution to deacetylate chitosan. Chitosan usually has a certain hydrophilicity, but the acetyl groups present therein will reduce the solubility of chitosan and the effect of modification. Through the deacetylation process, part of the acetyl groups can be removed, and the amino groups on the chitosan molecular chain can be increased, thereby enhancing its hydrophilicity and solubility in aqueous solution. In addition, the amino groups on the chitosan molecular chain after deacetylation can provide more reactive sites, which is convenient for subsequent functionalization reactions;
[0065] S2, dissolving phthalic anhydride in DMF to obtain a phthalic anhydride solution, slowly adding the freeze-dried chitosan in S1 to the phthalic anhydride solution, stirring the reaction mixture and pouring it into an ice alcohol solution, filtering it after precipitation, washing the precipitate with an alcohol solution until no reactant remains, and vacuum drying it to obtain phthalated chitosan.
[0066] The amino group reacts with the cyclic anhydride in a solvent such as DMF (N,N-dimethylformamide) to form a new structure introducing a cyclic imide, which protects specific groups during the chemical modification process, thereby ensuring that in subsequent reactions, specific hydroxyl groups in the chitosan molecule are modified without affecting other parts of the molecule, thereby improving the selectivity of the reaction.
[0067] S3, adding thionyl chloride and phthalated chitosan to pyridine, stirring for reaction and then cooling, filtering the precipitate, and vacuum drying the precipitate to obtain chlorinated chitosan.
[0068] The introduction of chlorinated groups can introduce new chemically active sites on the chitosan molecule to facilitate subsequent grafting
[0069] S4, adding sodium hydride into anhydrous tetrahydrofuran, adding methoxy polyethylene glycol, stirring once to deprotonate the methoxy polyethylene glycol, then slowly adding chitosan chloride, stirring twice, after the reaction is completed, pouring into an ice alcohol solution, filtering after precipitation, and vacuum drying to obtain polyethylene glycol phthalyl chitosan.
[0070] The present invention strictly limits the raw material to methoxy polyethylene glycol, and does not use polyethylene glycol. The reason is that the use of polyethylene glycol will introduce two hydroxyl ends into the reaction system, thereby generating a variety of different reaction products. The two hydroxyl ends will undergo a double substitution reaction with chlorinated chitosan, resulting in cross-linking or multi-point grafting, and thus the preparation of the target product cannot be achieved.
[0071] S5. Add polyethylene glycol-modified phthaloyl chitosan to a sodium hydroxide solution, stir for reaction, neutralize the reaction solution dropwise with dilute hydrochloric acid until it is neutral, then add the reaction mixture to an ice alcohol solution for precipitation, wash the precipitate with an alcohol solution to remove residual alkali and by-products, remove the phthaloyl group, restore the amino functional group of chitosan, and vacuum dry to obtain polyethylene glycol-modified chitosan.
[0072] In one embodiment, in S1, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0073] In one embodiment, the concentration of the alkaline solution is 40 wt % to 50 wt %.
[0074] In one embodiment, in S1, the reaction temperature is 80°C to 110°C, and the reaction time is 4 to 12 hours.
[0075] In one embodiment, the weight-to-volume ratio of the chitosan to the alkaline solution is 1 g: (20-50) mL. In one embodiment, the weight-to-volume ratio of the chitosan to the alkaline solution is 1 g: 25 mL.
[0076] In one embodiment, in S2, the concentration of the phthalic anhydride solution is 1 mol / L.
[0077] In one embodiment, in S2, the reaction temperature is 110°C to 120°C, and the reaction time is 6 to 10 hours.
[0078] In one embodiment, in S2, the reaction temperature is 120° C. and the reaction time is 6 hours.
[0079] In one embodiment, in S2, the weight-to-volume ratio of freeze-dried chitosan to phthalic anhydride solution is 1 g: (10-30) mL.
[0080] In one embodiment, in S2, the weight-to-volume ratio of freeze-dried chitosan to phthalic anhydride solution is 1 g:20 mL.
[0081] In one embodiment, in S3, the mass ratio of thionyl chloride to phthalated chitosan is (5-10):1.
[0082] In one embodiment, in S3, the mass ratio of thionyl chloride to phthalated chitosan is 8:1.
[0083] In one embodiment, in S3, the weight volume ratio of thionyl chloride to pyridine is 1 g: (15-30) mL.
[0084] In one embodiment, the weight volume ratio of thionyl chloride and pyridine is 1 g:20 mL.
[0085] In one embodiment, in S3, the reaction temperature is 50°C to 100°C, and the reaction time is 30 to 60 minutes.
[0086] In one embodiment, in S3, the reaction temperature is 80° C. and the reaction time is 45 min.
[0087] In one embodiment, the weight volume ratio of the sodium hydride to anhydrous tetrahydrofuran is (0.1-0.5) g / L. In one embodiment, the weight volume ratio of the sodium hydride to anhydrous tetrahydrofuran is 0.2 g / L.
[0088] In one embodiment, in S4, the stirring temperature is 50° C. to 70° C., and the stirring time is 0.5 to 3 h.
[0089] In one embodiment, in S4, the stirring temperature is 50° C. and the stirring time is 2 h.
[0090] In one embodiment, in S4, the secondary stirring temperature is 50° C. to 70° C., and the stirring time is 10 to 20 hours.
[0091] In one embodiment, in S4, the stirring temperature is 50° C. and the stirring time is 12 h.
[0092] In one embodiment, in S4, the concentration of the sodium hydroxide solution is 4 wt %.
[0093] In one embodiment, in S4, the weight volume ratio of PEGylated phthalyl chitosan to sodium hydroxide solution is (3-4) mg:1 mL.
[0094] In one embodiment, in S4, the weight volume ratio of PEGylated phthalyl chitosan to sodium hydroxide solution is 3 mg:1 mL.
[0095] In one embodiment, in S4, the reaction temperature is 80°C to 90°C, and the reaction time is 2 to 10 hours.
[0096] In one embodiment, in S4, the reaction temperature is 85° C. and the reaction time is 8 h.
[0097] In one embodiment, the alcohol solution is anhydrous ethanol or anhydrous methanol.
[0098] In one embodiment, the preparation process of polyethylene glycol-modified chitosan is carried out in an inert gas environment.
[0099] There are many methods for polyethylene glycol-modified chitosan, mainly including chemical grafting and physical blending. Among them, the physical blending method refers to preparing a blended material by physically mixing chitosan and PEG. In the research process, the present invention tested the polyethylene glycol-modified chitosan obtained by the physical blending method as a raw material for a scale inhibitor, but the results showed that no matter how the amount of addition and the ratio between the chitosan and other raw materials were changed, no good effect was achieved. Therefore, although the ethylene glycol-modified chitosan obtained by the physical blending method has the advantages of simple operation method and low cost, it is not suitable for the present invention.
[0100] Afterwards, the present invention further explored the modification method of the chemical grafting method, which includes two grafting modification ideas, namely acylation grafting modification and etherification grafting modification. The results show that although the modified chitosan obtained by the acylation reaction also has good performance, the mechanical strength and stability of the material are not good. Compared with the modified chitosan obtained by the etherification reaction, it will shorten the service life of the scale inhibitor and the stability of the material during use. Therefore, the present invention strictly limits the modification method of polyethylene glycol-modified chitosan to etherification grafting modification. As for the modification method, the present invention provides a method that can be achieved and does not require complex purification of the sample after preparation. But in principle, as long as the etherification modification at a specific site can be achieved to form an ether bond, it can be used in the preparation of the composite scale inhibitor product of the present invention.
[0101] In one embodiment, the preparation method of EDTA-chitosan is as follows:
[0102] Chitosan was dissolved in acetic acid solution, EDTA-2Na was added, the pH value was adjusted to 5.0 with 5 mol / L sodium hydroxide solution, carbodiimide (EDAC) was added, stirred for reaction, and then the reaction solution was dialyzed and freeze-dried to obtain EDTA-chitosan.
[0103] In one embodiment, the concentration of the acetic acid solution is 0.1% to 3% (v / v).
[0104] In one embodiment, the weight volume ratio of chitosan to acetic acid solution is 0.1 g:1 mL.
[0105] In one embodiment, the weight ratio of chitosan to EDTA-2Na is 1:2.
[0106] In one embodiment, the reaction temperature is room temperature and the reaction time is 4 hours.
[0107] In one embodiment, the concentration of the carbodiimide is 40 mmol / L.
[0108] The present invention also provides a method for preparing the composite antiscalant, which specifically comprises the following steps:
[0109] Weigh the raw materials according to the proportion, mix them evenly and stir them to obtain the composite scale inhibitor.
[0110] In one embodiment, the stirring temperature is 20° C. to 50° C., and the stirring time is 5 to 15 minutes.
[0111] The technical solution provided by the present invention is further described below in conjunction with embodiments.
[0112] Unless otherwise specified, all experiments were repeated three times. SPSS21.0 was used for analysis of variance (ANOVA) and Duncan's multiple comparison analysis. The results were expressed as mean ± standard deviation, and P < 0.05 indicated a significant difference. Origin2021 was used for drawing.
[0113] Example 1
[0114] A composite antiscalant, composed of the following raw materials in parts by weight:
[0115] 5 parts of polyethylene glycol-modified chitosan, 25 parts of EDTA-chitosan, 15 parts of polyacrylic acid, 5 parts of citric acid, and 85 parts of water;
[0116] The weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:5.
[0117] The preparation method of the polyethylene glycol modified chitosan is as follows:
[0118] S1, chitosan and 50wt% potassium hydroxide solution were mixed in a weight volume ratio of 1g:25mL, stirred at 100°C for 6h, filtered, and freeze-dried;
[0119] S2, dissolving 1 mol / L phthalic anhydride in DMF to obtain a phthalic anhydride solution, mixing the freeze-dried chitosan in S1 and the phthalic anhydride solution at a weight volume ratio of 1 g: 20 mL, stirring at 120° C. for 6 h, pouring the reaction mixture into iced anhydrous ethanol, filtering after precipitation, washing the precipitate with an alcohol solution until no reactant remains, and vacuum drying to obtain phthalated chitosan;
[0120] S3, adding thionyl chloride and phthalated chitosan to pyridine in a weight volume ratio of thionyl chloride to pyridine of 1 g:20 mL and a mass ratio of thionyl chloride to phthalated chitosan of 8:1, stirring at 80° C. for 45 min, cooling, filtering the precipitate, and vacuum drying the precipitate to obtain chlorinated chitosan;
[0121] S4, adding sodium hydride to anhydrous tetrahydrofuran at a weight volume ratio of 0.2 g / L, adding methoxy polyethylene glycol, stirring at 50° C. for 2 h to deprotonate the methoxy polyethylene glycol, then slowly adding chlorinated chitosan, stirring at 50° C. for 12 h, pouring into iced anhydrous ethanol after the reaction is completed, filtering after precipitation, and vacuum drying to obtain PEGylated phthaloyl chitosan;
[0122] S5. Add polyethylene glycol-modified phthalyl chitosan to 4 wt % sodium hydroxide solution in a weight volume ratio of 3 mg:1 mL. After stirring at 85° C. for 8 h, neutralize the reaction solution dropwise with dilute hydrochloric acid until it is neutral. Then, add the reaction mixture to ice-cold anhydrous ethanol for precipitation. Wash the precipitate with an alcohol solution to remove residual alkali and by-products. Then, dry it in vacuum to obtain polyethylene glycol-modified chitosan.
[0123] The preparation process of the polyethylene glycol-modified chitosan is carried out in a nitrogen atmosphere.
[0124] The preparation method of the EDTA-chitosan is as follows:
[0125] Chitosan was dissolved in 0.5% (v / v) acetic acid solution at a weight volume ratio of 0.1 g:1 mL of chitosan to acetic acid solution, EDTA-2Na was added in an amount twice the weight of chitosan, the pH value was adjusted to 5.0 with a 5 mol / L sodium hydroxide solution, carbodiimide was added to a concentration of 40 mmol / L, the reaction was stirred at room temperature for 4 h, the reaction solution was dialyzed, and freeze-dried to obtain EDTA-chitosan.
[0126] The preparation method of the composite scale inhibitor is as follows: weigh raw materials according to proportion, mix the raw materials evenly, and stir at 20° C. for 15 minutes to obtain the composite scale inhibitor.
[0127] Example 2
[0128] The same as Example 1, except that: the composite scale inhibitor is composed of the following raw materials in parts by weight:
[0129] 2 parts of polyethylene glycol-modified chitosan, 10 parts of EDTA-chitosan, 10 parts of polyacrylic acid, 2 parts of citric acid, and 100 parts of water.
[0130] Example 3
[0131] The same as Example 1, except that: the composite scale inhibitor is composed of the following raw materials in parts by weight:
[0132] 10 parts of polyethylene glycol-modified chitosan, 30 parts of EDTA-chitosan, 25 parts of polyacrylic acid, 8 parts of citric acid, and 80 parts of water.
[0133] Comparative Example 1
[0134] The same as Example 1, except that: the composite scale inhibitor does not contain polyethylene glycol-modified chitosan, and the amount of EDTA-chitosan is adjusted to 30 parts by weight accordingly.
[0135] Comparative Example 2
[0136] The same as Example 1, except that the polyethylene glycol-modified chitosan in the composite scale inhibitor is prepared by blending and modification, and the specific method is as follows:
[0137] Chitosan and polyethylene glycol were dissolved in 5% acetic acid solution to prepare a 1% solution. 60% chitosan solution and 40% polyethylene glycol solution were added to a flask equipped with a stirrer and a thermometer and placed in a constant temperature water bath. The pH value was adjusted and mixed evenly. The mixture was reacted at 30°C for 5 hours, and then the negative ion material was added and the temperature was increased to 50°C. After keeping warm for 1 hour, the reaction was stopped and the final product was obtained (Yao Qingda, Liang Yongxian, Wang Xiaozhuo, et al. Preparation and Application of Chitosan / Polyethylene Glycol Modified Negative Ion Leather Finishing Agent [J]. Leather and Chemical Industry, 2020, 37(3):8.).
[0138] Comparative Example 3
[0139] The same as Example 1, except that: the composite scale inhibitor does not contain EDTA-chitosan, and the amount of polyethylene glycol-modified chitosan is adjusted to 30 parts by weight accordingly.
[0140] Comparative Example 4
[0141] Same as Example 1, except that the weight ratio of polyethylene glycol-modified chitosan to EDTA-chitosan is 1:1, that is, 15 parts by weight of polyethylene glycol-modified chitosan and 15 parts by weight of EDTA-chitosan.
[0142] Test Example 1 Effect of temperature on the scale inhibition performance of composite scale inhibitor
[0143] Scale inhibition performance testing method:
[0144] Configuration CaCO3 Ca 2+ The solution with a mass concentration of 250 mg / L was placed in a water bath at 80°C for 10 hours, then cooled and filtered, and the Ca content in the filtrate was determined. 2+ Content, calculate the scale inhibition rate of CaCO3.
[0145] Configuration CaSO4 Ca 2+ The solution with a concentration of 5000 mg / L was placed in a water bath at 80°C for 10 hours, then cooled and filtered, and the Ca content in the filtrate was determined. 2+ Content, calculate the scale inhibition rate of CaSO4.
[0146] The scale inhibition rate of the composite scale inhibitor (50 mg / L) of Example 1 on CaCO3 and CaSO4 was tested at different temperatures. The results are as follows: Figure 1 shown.
[0147] Depend on Figure 1It can be seen that with the increase of temperature, the scale inhibition effect of the scale inhibitor on CaCO3 and CaSO4 decreases to a certain extent, but at 110°C, the scale inhibition rate of the scale inhibitor still remains at about 95%, indicating that the composite scale inhibitor of the present invention still has a good scale inhibition effect (scale inhibition rate of more than 95%) even under high temperature conditions, which shows that it can still maintain good scale inhibition at higher temperatures.
[0148] The scale inhibition performance of the scale inhibitors in other embodiments and comparative examples at 110° C. was tested, and the results were as follows:
[0149]
[0150] The results show that the chitosan modified by polyethylene glycol grafting etherification plays an important role in improving the scale inhibition effect of the composite scale inhibitor at higher temperatures, and the synergistic effect between polyethylene glycol-modified chitosan and EDTA-chitosan is limited by the ratio between the two. Under a specific ratio, it has a positive effect on improving the scale inhibition rate, while the increase in the content of polyethylene glycol-modified chitosan will have a counter-effect. At the same time, the test results show that the scale inhibition rate change trends of CaCO3 and CaSO4 under different embodiments are basically the same.
[0151] Test Example 2 Effect of Metal Ions on the Antiscaling Performance of Antiscalants
[0152] Configuration CaCO3 Ca 2+ The mass concentration is 250 mg / L, Mg 2+ The concentration is 100ppm, Al 3+ Concentration of 1ppm, Fe 3+ The solution with a concentration of 1.5 ppm was placed in a water bath at 80 °C for 10 h, then cooled and filtered, and the Ca content in the filtrate was determined. 2+ Content, calculate the scale inhibition rate of CaCO3.
[0153] Configuration CaSO4 Ca 2+ The concentration of 5000mg / L solution, Mg 2+ The concentration is 100ppm, Al 3+ Concentration of 1ppm, Fe 3+ The solution with a concentration of 1.5 ppm was placed in a water bath at 80 °C for 10 h, then cooled and filtered, and the Ca content in the filtrate was determined. 2+ Content, calculate the scale inhibition rate of CaSO4.
[0154] The scale inhibition performance of the example and comparative example scale inhibitor (50 mg / L) at 110° C. was tested, and the results are as follows:
[0155]
[0156]
[0157] Generally speaking, metal ions such as magnesium, aluminum, and iron have a significant effect on the antiscaling effect of scale inhibitors. Magnesium ions easily form insoluble magnesium hydroxide and magnesium carbonate in water, and these precipitates will affect the effect of scale inhibitors. The chelation effect of magnesium ions with scale inhibitors is weak, so the effect of scale inhibitors will be reduced at high magnesium ion concentrations. Aluminum ions easily form aluminum hydroxide precipitates in water, and these precipitates will react with scale inhibitors, affecting their dispersion and chelation. When the aluminum ion concentration is high, the effect of scale inhibitors will also be affected to a certain extent. Iron ions have the most significant effect on scale inhibitors. Iron ions easily react with the active ingredients in scale inhibitors to form insoluble iron compounds, which significantly reduce the effect of scale inhibitors. Especially at high iron ion concentrations, the antiscaling effect of scale inhibitors will drop significantly.
[0158] The results show that the present invention adopts the compound of polyethylene glycol-modified chitosan and EDTA-chitosan, so that the composite scale inhibitor still has a good scale inhibition effect in the presence of metal ions, thereby being able to meet the scale inhibition needs of more types of industrial water.
[0159] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A composite scale inhibitor, characterized in that: The invention comprises the following raw materials in parts by weight: 2-10 parts of polyethylene glycol-modified chitosan, 5-30 parts of EDTA-chitosan, 10-25 parts of polyacrylic acid, 2-8 parts of citric acid, and 80-100 parts of water; The weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:(3-5); The polyethylene glycol-modified chitosan is prepared by using polyethylene glycol and chitosan as raw materials and undergoing etherification grafting modification, and specifically comprises the following steps: S1, adding chitosan to an alkaline solution, stirring for reaction, filtering, and freeze-drying; S2, dissolving phthalic anhydride in DMF to obtain a phthalic anhydride solution, slowly adding the freeze-dried chitosan in S1 to the phthalic anhydride solution, stirring the reaction mixture, pouring it into an ice alcohol solution, filtering it after precipitation, washing the precipitate with an alcohol solution until no reactant remains, and vacuum drying it to obtain phthalated chitosan; S3, adding thionyl chloride and phthalated chitosan to pyridine, stirring for reaction and then cooling, filtering the precipitate, and vacuum drying the precipitate to obtain chlorinated chitosan; S4, adding sodium hydride to anhydrous tetrahydrofuran, adding methoxy polyethylene glycol, stirring once to deprotonate the methoxy polyethylene glycol, then slowly adding chlorinated chitosan, stirring twice, pouring into an ice alcohol solution after the reaction is completed, filtering after precipitation, and vacuum drying to obtain polyethylene glycol phthalyl chitosan; S5. Add polyethylene glycol-modified phthalyl chitosan to a sodium hydroxide solution, stir for reaction, neutralize the reaction solution dropwise with dilute hydrochloric acid until it is neutral, then add the reaction mixture to an ice alcohol solution for precipitation, wash the precipitate with an alcohol solution to remove residual alkali and by-products, and vacuum dry to obtain polyethylene glycol-modified chitosan.
2. The composite antiscalant according to claim 1, characterized in that: The weight ratio of the polyethylene glycol-modified chitosan to the EDTA-chitosan is 1:
5.
3. The composite antiscalant according to claim 1, characterized in that: The composite antiscalant comprises the following raw materials in parts by weight: 5 parts of polyethylene glycol-modified chitosan, 25 parts of EDTA-chitosan, 15 parts of polyacrylic acid, 5 parts of citric acid, and 85 parts of water.
4. The method for preparing the composite scale inhibitor according to any one of claims 1 to 3, characterized in that: The following steps are involved: Weigh the raw materials according to the proportion, mix them evenly and stir them to obtain the composite scale inhibitor.
5. The preparation method according to claim 4, characterized in that: The stirring temperature is 20°C to 50°C, and the stirring time is 5 to 15 min.
6. Use of the composite scale inhibitor according to any one of claims 1 to 3 in chemical wastewater treatment.
7. The use according to claim 6, characterized in that: The dosage of the composite scale inhibitor is 20-100 mg / L.